Çevrimiçi Forum Yazarlarının Bakış Açısından Türkiye de Müzik ve Müzik Eğitiminin Görünümü - SEVER, Gülşah; ÖZOK, Ezgi; AYAZ TÖRAL, Dilara; SİVRİ ÖZKARADİĞİN, Begüm (Dicle Üniversitesi Ziya Gökalp Eğitim Fakültesi Dergisi, 2023)
Bu araştırma çevrimiçi forum yazarlarının bakış açısından müzik ve müzik eğitiminin incelenmesini amaçlamaktadır. Araştırma, nitel araştırma desenlerinden durum çalışmasıdır. Araştırmada veri kaynağı olarak çevrimiçi forum sitelerindeki forum yazıları temel alındığı için veri toplama yöntemi olarak doküman analizi kullanılmıştır. İçerik analizi sonucunda müzik, müzik eğitimi ve müzik dışı konular olmak üzere üç farklı tema ortaya çıkmıştır. Forum yazarlarının görüşleri müzik teması altında müzik yazılımları ve kaynak; müzik eğitimi teması altında sınav, eğitim tartışmaları, eğitim plan/program paylaşımı ve deneyim paylaşımı; müzik dışı konularda ise vefat haberleri ve özel gün kutlama başlıkları altında kategorize edilmiştir. Forum yazarlarının yoğunluklu olarak yazılım/nota/kitap/altyapı/ders planı paylaşımları ile müzik eğitim kurumlarının sınavlarına hazırlık amacıyla forumda etkileşime girdikleri belirlenmiştir. This research aims to examine music and music education from the perspective of online forum writers. The research is a case study from qualitative research designs. Since the research is based on forum posts on online forum sites as data sources, document analysis was used as the data collection method. The research is a case study of qualitative research designs with this structure. Since the forum articles on muzikegitimcileri.net were used as the data source in the research, document analysis was used as the data collection method. As a result of the content analysis, three themes emerged: music, music education, and non-music subjects. The opinions of forum writers are categorized under the theme of music, including music software and resources. Under the theme of music education, topics such as exams, educational discussions, sharing of education plans/programs, and sharing of experiences are categorized. In non-music-related topics, categorization is done under obituaries and special day celebration headings. It was determined that the forum authors interacted intensively in the forum to prepare for the examinations of music education institutions by sharing software/notes/books/infrastructure/lesson plans. It is recommended to establish and enhance platforms that inform students, especially about the content, preparation, and outcomes of entrance exams.